Hydrogel patch from liquid smoke and vitamin K Collard Greens extract for wound healing applications. Issue 1 (May 2021) - Saputra, S; Wibisono, G; Ramadhani, E; Dewi, T
Abstract: Wound care by using wound dressing has been evolved available in various physical forms including hydrogels with the highest global use reaching 43%. Nowadays, hydrogels are available at high cost because produced from synthetic materials, so natural materials are needed to obtain antibacterial wound dressing. This study aims to analyze the hydrogel patch PVA/chitosan/starch infused liquid smoke and vitamin K collard greens extract which are antibacterial effects and accelerates wound healing. This study was a laboratory experiment. Collard greens were extracted by using the Direct Solvent Extraction II method. The membrane characteristic tested using SEM test. The parallel streak method (AATCC 147-2004) was used for antibacterial testing. The hydrogel patch application was carried out on 28 male Rattus norvegicus strain wistar rats. They were given incisions wound and treated by a control group and 3 treatment groups and conducted wound healing analysis on the 4 th, 7 th, 11 th and 14 th day observation. The antibacterial test showed the hydrogel patch infused liquid smoke with a concentration of 12% was the optimum concentration inhibiting S. aureus . In conclusion, the hydrogel patch has a smooth and porous surface, can be inhibited the growth of S. aureus, and proven to completely heal the animal wound.